2016
DOI: 10.3390/healthcare4010013
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal Disorders and Working Posture among Dental and Oral Health Students

Abstract: The prevalence of musculoskeletal disorders (MSD) in the dental professions has been well established, and can have detrimental effects on the industry, including lower productivity and early retirement. There is increasing evidence that these problems commence during undergraduate training; however, there are still very few studies that investigate the prevalence of MSD or postural risk in these student groups. Thus, the aim of this study was to determine the prevalence of MSD and conduct postural assessments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
96
2
14

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(123 citation statements)
references
References 22 publications
11
96
2
14
Order By: Relevance
“…Although the dental students′perception has not been affected by gender and presence of pain, some studies have reported higher perception scores and pain complaints by women, which indicates that they pay more attention to biological factors and adapt less to their work environment…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Although the dental students′perception has not been affected by gender and presence of pain, some studies have reported higher perception scores and pain complaints by women, which indicates that they pay more attention to biological factors and adapt less to their work environment…”
Section: Discussionmentioning
confidence: 97%
“…The lack of knowledge in ergonomics can have contributed to these findings. Several authors have supported the teaching of ergonomics in the undergraduate curriculum . According to them, preventive educational programmes are essential to enhance students′ knowledge about ergonomics and allow early detection of their musculoskeletal disorders.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[10] Diş hekimliği bö-lümünde okuyan öğrenciler ile yapılan bir çalışmada en fazla yaşanılan ağrının bel ve boyun ağrısı olduğu belirlenmiştir. [11] Tayland üniversitesinde öğrenci-lerin bel ağrısı yaşama durumlarının incelendiği bir araştırmada, öğrencilerin %31'i, diğer bir çalışmada %42,8'i son bir yıl içerisinde bel ağrısı yaşadıklarını belirtmişlerdir. [12,13] Diğer araştırmalarda da bizim ça-lışmamızda olduğu gibi öğrencilerin yaklaşık üçte biri bel ağrısı sorunu yaşamaktadır.…”
Section: Pain a Riunclassified